2011
DOI: 10.1007/s10695-011-9536-6
|View full text |Cite
|
Sign up to set email alerts
|

Live chilling of Atlantic salmon: physiological response to handling and temperature decrease on welfare

Abstract: Investigation of the physiological effects of live chilling in Atlantic salmon, Salmo salar, has been performed in two experiments. In the first, fish (mean weight 840 g) acclimatized to either 16, 8, or 4°C were directly transferred horizontally or vertically (9 combinations) to water temperatures of 16, 8, 4, or 0°C using a dip net. Blood samples were collected at 1 and 6 h (h) post-transfer. In the second experiment, fish (mean weight 916 g) acclimatized to 16°C were exposed to four temperature-drop regimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Both dissolved oxygen and pH were however, within the requirements for silver catfish (Baldisserotto & Silva, ). Despite being resistant to low temperature (Barcellos, Woehl, Wassermann, Quevedo, Ittzes, & Krieger, ), silver catfish can be stressed by the low temperature used in the hypothermia tank as Atlantic salmon, which are also resistant to low temperature, did show pain and suffering when submitted to temperature drop from 16 to 0°C within 1 h (Foss, Grimsbo, Vikingstad, Nortvedt, Slinde, & Roth, ). Nile tilapia also showed increased levels of chemical indicators of stress after hypothermia stunning (Oliveira Filho, Girao, Melo, & Viegas, ).…”
Section: Discussionmentioning
confidence: 99%
“…Both dissolved oxygen and pH were however, within the requirements for silver catfish (Baldisserotto & Silva, ). Despite being resistant to low temperature (Barcellos, Woehl, Wassermann, Quevedo, Ittzes, & Krieger, ), silver catfish can be stressed by the low temperature used in the hypothermia tank as Atlantic salmon, which are also resistant to low temperature, did show pain and suffering when submitted to temperature drop from 16 to 0°C within 1 h (Foss, Grimsbo, Vikingstad, Nortvedt, Slinde, & Roth, ). Nile tilapia also showed increased levels of chemical indicators of stress after hypothermia stunning (Oliveira Filho, Girao, Melo, & Viegas, ).…”
Section: Discussionmentioning
confidence: 99%
“…Which factors are most relevant as stressors, pumping, live chilling or CO 2 ? With live chilling, Foss et al (2012) showed that, in a controlled environment, a temperature drop from 4 and 8 to 0°C has no significant stress effect. The observed stress effects in the presented study can only be explained by crowding, pumping and CO 2 alone.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in plasma lactate have been previously described for S. salar after physical handling (Foss et al . ), and in S. trutta infested with L. salmonis, where fish showed flashing behaviour (Wells et al . ).…”
Section: Discussionmentioning
confidence: 99%